"He Acted as If He Owned Me": An Exploratory Case Study Analysis of Correctional Staff Sexual Misconduct Against Women on Parole. (September 2021) - Fedock, Gina; Darcy, Kathleen M.; Kubiak, Sheryl
While the Prison Rape Elimination Act focuses on sexual victimization in correctional settings, staff-perpetrated sexual misconduct against women under community-based correctional supervision has received little attention. This study explored women's experiences of sexual victimization by correctional staff while on parole and used a case study approach to examine sexual victimization incidents experienced by ten women. Women described how staff's misuse of power permeated the abuse tactics. Officers used their status to gain access to women, applied individualized tactics with promises and threats, and controlled when the abuse ended. Practices and policies are needed to build safety for women under community-based correctional supervision.